Structural steelwork design to BS 5950: part 1 and EC3 (comparison and program development) / Jamal Ariffin - Ariffin, Jamal (1997)
The use of steel in building construction industry varies from country across the Asian region. In Malaysia, rapid development in building construction industry has stimulated all professionals and construction developers to recognise its strength and weakness and, even more importantly, its 'customers' needs, and hence to design the buildings in line with this recognition. This final year project paper was to compare in structural steelwork design by using different code of practice between Eurocode (EC3) and British Standard (BS 5950: Part 1). It was focused on simply-supported steel beam design and steel column design; by using universal beam, UB and universai column, UC. Computer packages on these design were developed. In Malaysia, BS 5950: Part 1 is very familiai for civil engineers, but Eurocode3 (EC3) is a new code of practice. Beyond 1999, all of the European countries will be using the Eurocode as a code of practice instead British Standard. Consequently, Malaysia also might be using Eurocode as its references for structural steelwork design. Hence, this project can give guidelines in the changes and differences between BS 5950: Part 1 and EC3.